The Effects of Guinea-Pig Gamma Globulins on Capillary Permeability and Serum Complement - Davies, G. E. (1961)
Gamma globulins, isolated from guinea-pig serum by five different methods, increased capillary permeability when injected intradermally into guinea pigs. None of the methods of isolation caused aggregation of the globulins as judged by ultracentrifugal analysis. The γ-globulin activity was not altered by heat (56° for 30 minutes) but was inhibited by albumin, soya-bean trypsin inhibitor and di-isopropylphosphofluoridate. All preparations inhibited serum complement but only when they had been freeze-dried.